Human Serum Albumin Binds Streptolysin O (SLO) Toxin Produced by Group A Streptococcus and Inhibits Its Cytotoxic and Hemolytic Effects - Vita, Gian Marco; De Simone, Giovanna; Leboffe, Loris; Montagnani, Francesca; Mariotti, Davide; Di Bella, Stefano; Luzzati, Roberto; Gori, Andrea; Ascenzi, Paolo; di Masi, Alessandra (Frontiers in Immunology, 2020)
.